Analysis of the association between symptoms referred by patients with endometriosis and the site of the disease - Berbel, Bruna Thomazelli; Podgaec, Sérgio; Abrão, Maurício Simões (Revista de Medicina, 2008)
Endometriosis is a disease characterized by ectopic implantation of stroma and/or endometrial glands in extra-uterine location that affects 15% of women in reproductive age and may be expressed in peritoneum, ovary or as deeply infiltrating lesions. Symptoms could be pelvic pain, which includes deep dyspareunia, dysmenorrhea and aciclic pain, infertility and intestinal and urinary cyclical changes. The diagnostic suspicion is made through suggestive clinical and image exams, but it depends on the confirmation by surgical procedures such as video-laparoscopy that allows viewing the pelvis and obtaining tissues samples for further histological analysis. Some researches had been done about the delay on diagnosis since the first symptoms and one of the major causes is the lack of knowledge of the patients and even the doctors about the disease, beyond the difficulty of access to laparoscopy procedures at the public health system. In order to find some relation between the sites of the disease and clinical data, many researches have been done and the most evident associations are: deep dyspareunia related to lesions in pouch of Douglas and severe dysmerorrhea related to the presence of pelvic pain in advanced stages of endometriosis. The present paper is a literature review to find some consistent relation between the characteristics of the disease and the symptoms, and to search for the bias of patient‘s selection or information, that undermined some of the researches. This is an attempt to allow the medical practice to make the diagnosis earlier.